Optimization of Photothermal Therapy Treatment Effect under Various Laser Irradiation Conditions - Kim, Donghyuk; Kim, Hyunjung (International Journal of Molecular Sciences, 2022)
The photothermal effect refers to a phenomenon in which light energy is converted into heat energy, and in the medical field, therapeutics based on this phenomenon are used for anticancer treatment. A new treatment technique called photothermal therapy kills tumor tissue through a temperature increase and has the advantages of no bleeding and fast recovery. In this study, the results of photothermal therapy for squamous cell carcinoma in the skin layer were analyzed nu-merically for different laser profiles, intensities, and radii and various concentrations of gold nano-particles (AuNPs). According to the heat‐transfer theory, the temperature distribution in the tissue was calculated for the conditions under which photothermal therapy was performed, and the therapeutic effect was quantitatively confirmed through three apoptotic variables. In addition, the laser intensity and the volume fraction of AuNPs were optimized, and the results provide useful criteria for optimizing the treatment effects in photothermal therapy.
Keywords: Cell Line, Tumor; Cell Survival; Gold; Metal Nanoparticles; Phototherapy; Photothermal Therapy; Temperature; apoptosis; bioheat transfer; gold nanoparticles; laser condition; photothermal therapy; squamous cell carcinoma; thermal damage